Pengurusan konservasi dalam konteks perkembangan urbanisasi di Taiping bandar warisan 1990-2020 - Rekha, Selvarajoo (2022)
A qualitative study to discuss the challenges and problems of conservation of historic buildings and sites in Malaysia has been conducted. This study aims to bridge the gap in research related to the conservation of historic buildings and sites in Taiping, Perak. As not much research or previous work has been done on conservation of historic buildings and sites in Taiping, this study aims to specifically study the management of historical buildings and sites as well as analyzing the challenges and problems related to such efforts. This study uses library research methods and archive research that relies on documents and files from government offices and agencies as the main source of information. The findings of the study have identified several problems in conservation of historic buildings and sites in Taiping. These include, lack of awareness and understanding on importance of conservation, poor skill and shallow experience among conservation workers, high consultation, equipment, machinery and wages costs, dilemma between conservation and reconstruction (reconstruction is easier and cheaper, but reduces the historical value of a monument), the dilemma between the value of heritage and development (most historic buildings and sites are located on vast areas that have the potential for commercial development), bureaucratic perversions and misinterpretations of the law, whereby there is a significant overlap of powers and roles between the government departments and agencies involved. In conclusion, historic buildings and sites are invaluable national assets and heritage, and contributes towards the country's economic growth through the tourism industry. Therefore, government should use a thoughtful approach to preserve and conserve these historic and heritage buildings.